Use of Unannounced "Mystery Patient Drills" to Assess Hospital Emergency Department Preparedness for Communicable Diseases of Public Health Concern in New York City, 2016. (4th October 2017) - Foote, Mary; Styles, Timothy; Quinn, Celia
Abstract: Background: Recent infectious disease epidemics have highlighted the importance of rapid recognition and isolation of patients with severe infectious diseases. In response, the New York City Department of Health and Mental Hygiene carried out a series of unannounced "Mystery Patient Drills" to assess Emergency Departments (ED) ability to identify and safely respond to patients with communicable diseases of public health concern. Methods: All 911-receiving hospitals participating in the NYC Hospital Preparedness Program were recruited to participate. Scenarios utilized an actor presenting to an ED describing symptoms and history consistent with measles or MERS-CoV. An exercise evaluation guide captured performance measures to analyze 1) compliance with key infection control measures; 2) association between screening interventions (e.g., travel history) and implementation of infection control measures; 3) times from patient entry to triage, donning a mask, and placement into isolation. Post-drill report narratives were reviewed to identify additional strengths and challenges. Results: Among 50 eligible hospitals, 49 participated in 2 drills ( N = 98) during December 2015–May 2016. Three pilot drills were excluded from the analysis. The patient was masked and isolated in 78% of drills; 61% of hospitals completed this process in both drills. Masking and isolation was observed in a higher proportion of drills when travel history was obtained, compared with drills when travel history was not obtained (88% vs. 21%; P < 0.0001). The median time from patient entry to masking was 1 minute and 9 minutes to placement into isolation. Overall, 36% of staff practiced hand hygiene and 77% entered the isolation room wearing Personal Protective Equipment. Identified best practices include the use of triage questionnaires to identify high-risk patients and algorithms to guide masking and isolation procedures. Conclusion: ED staff's ability to identify potentially infectious patients and implement recommended control measures varied. Drill findings were used to inform hospital improvement planning and will guide citywide efforts to improve healthcare system readiness for communicable diseases through addressing identified gaps and supporting implementation of best practice recommendations. Disclosures: All authors: No reported disclosures.